Evidence for space-charge-limited conduction in organic photovoltaic cells at open-circuit conditions - Di Nuzzo, Daniele; Reenen, Stephan van; Janssen, René A. J.; Kemerink, Martijn; Meskers, Stefan C. J. (Physical review. B, Condensed matter and materials physics, 2013)
The ac admittance of solar cells under illumination is investigated under open-circuit conditions. Open-circuit conditions are imposed by inserting a probe capacitor into the circuit. The capacitance and conductance of the cells are investigated as function of frequency and continuous illumination intensity. Results are compared with numerical and analytical modeling of charge recombination and transport. In bulk heterojunction solar cells with [6,6]-Phenyl-C61(C71)-butyric acid methyl ester as acceptor and poly(3-hexylthiophene) or poly[2-methoxy-5-(2′-ethylhexyloxy)-p-phenylene vinylene] as electron donor, the high-frequency capacitance C and conductance G follow a power-law dependence on intensity of white light I, with G(I) ∝ I3/4 and C(I) ∝ I1/4. The modeling shows that these dependencies can be explained in terms of space-charge-limited current in combination with Langevin type recombination of carriers. For poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b:3,4-b′]dithiophene-2,6-diyl]] the capacitance shows a weaker dependence on intensity, indicating fast recombination of photogenerated carriers. Results indicate that the fill factor of relatively well performing polymer solar cells can still be limited by space charge effects and can be improved by enhancing the charge carrier mobility or by reducing the bimolecular Langevin recombination.